Dietary and phytogenic inclusion effects on the broiler chicken cecal ecosystem - Palamidi, Irida; Paraskeuas, Vasileios V.; Mountzouris, Konstantinos C. (Frontiers in Animal Science, 2023)
Dietary modulation in broilers is crucial for the establishment of beneficial microbiota and, subsequently, the promotion of intestinal health. In this trial, a 2 × 2 factorial design was used with two different specifications with respect to dietary metabolizable energy (ME) and crude protein (CP) levels (i.e., 95% and 100% of recommendations) and phytogenic levels (0 and 150 mg/kg). Levels of total bacteria, Bacteroides spp., Lactobacillus spp., and Clostridium cluster XIVa attached to the cecal mucosa and in the cecal digesta were lower in broilers fed the 95% ME and CP specification diets, as was the molar ratio of butyric acid. In addition, the relative activity of autoinducers-2 (AI-2) and the expression levels of TLR4 and AvBD6 were increased. Phytogenic supplementation reduced cecal digesta levels of Escherichia coli and Clostridium cluster I levels, and increased Clostridium cluster IV levels. Moreover, the butyric acid molar ratio and the relative activity of AI-2 were increased, whereas the concentration of branched VFAs and the expression of AvBD6 and LEAP2 were reduced by phytogenic administration. Dietary specifications and phytogenic interactions were shown for the cecal-attached microbiota composition, metabolic activity of digesta microbiota, relative expression of autoinducers-2, and relative expression of toll-like signaling molecules and host antimicrobial peptides. In conclusion, it has been shown that ME and CP dietary specifications, combined or not with phytogenics, modulate multilevel gut biomarkers ranging from microbiota composition and metabolic activity to microbial communications and host signaling, inflammation, and defense.